Pengaruh Pemberian Makanan Tambahan Pangan Lokal Terhadap Status Gizi Ibu Hamil KEK - Nurul Hidayah Dariyatmo; Yesi Arisonaidah (Sistem Informasi, 2023)
WHO states the prevalence of Chronic Energy Deficiency (CED) is 35-75% in pregnancy. Even in developing countries, 40 percent of maternal deaths are caused by a lack of protein energy during pregnancy. RISKESDAS 2018 data found that the proportion of pregnant women with CED in Indonesia was 17.3%. The risk for pregnant women with CED is sudden death during childbirth or the risk of low birth weight babies. Provision of additional food (PMT) for local steamed sponge cake can be an effort to improve nutrition. The research objective was to determine the effect of PMT local food on the nutritional status of pregnant women with CED. Type of quantitative research design Quasi experimental design One Group Pre test and Post test. The population of this study is KEK pregnant women, the sampling technique is consecutive sampling. Sample 10 respondents. Research shows Pvalue 0.005 < α 0.05. In conclusion, the provision of local food additives for steamed sponge cake has an effect on the nutritional status of pregnant women with CED. It is suggested to the Puskesmas to vary the PMT menu with local food menus as a snack for pregnant women.